A new species of Rock-Dwelling Scinax Wagler (Anura: Hylidae) from Chapada dos Veadeiros, Central Brazil - de Araujo Vieira, Katyuscia (2015)
A new species of the Scinax ruber clade is described from Chapada dos Veadeiros region, Central Brazil. The new species is diagnosed by having SVL 21.9-27.7 mm in males and 26.7-31.7 mm in females; snout acuminate in dorsal view and rounded in profile; medium-sized tympanum; vocal sac single, median, subgular, that does not reach the pectoral region; iris iridescent yellow, with some thin, darker reticulations; tadpoles with ventral oral disc; P-3 regular and unmodified as a labial arm; absence of keratinized and colored plates on the sides of the lower jaw-sheath; presence of a keratinized and colored spur on each side behind the lower jaw-sheath; dorsolateral eyes, ventrally invisible; and advertisement call composed of 8-14 notes each with 4-18 pulses, and duration of 290-420 ms. The new species uses temporary creeks in rock meadows above 1.000 m a.s.l. and males calls from rock outcrops. The dorsal color pattern enables this species to camouflage in this kind of surfaces.